Strategies and challenges for the promotion of a responsibility mindset in technical career students during internships - Zavala-Pérez, Jose María; Jiménez-Rivero, Ana; García-Navarro, Justo (Advances in Building Education, 2021)
Promoting responsibility values and knowledge of students requires actions with a strong focus on citizenship and ethics, with the aim to commit, engage, and empower future professionals. In this sense, a key question arises: how to define and foster responsibility among professionals at different organizational levels? This paper deals with contextual factors and key concepts for promoting responsibility-related values and competences (knowledge, skills, attitudes) throughout curricular internships carried out by students of technical degrees. In this work, we explore the advantages and challenges of working on a responsibility approach at this stage of a professional career, and we outline ideas for optimizing the process.